Specific and non-specific interactions between ammonia and activated carbons - Stoeckli, Fritz; Guillot, André; Slasli, Abdou (My University, 2004)
It is shown that the adsorption of NH3 by activated carbons at different temperatures follows Dubinin's theory and, as in the case of water, for carbons with high oxygen contents one observes an upward deviation in the initial section of the DR plot. This indicates a strong primary adsorption, due to specific interactions. At higher relative pressures, this adsorption is followed by a classical micropore filling mechanism, where NH3 conforms to the pattern of non-specific adsorption. The affinity coefficient β1 (NH3) associated with primary adsorption varies between 0.4 and 1.2. It depends on the characteristic energy E0 and on the ratio between the amount of oxygen present on the surface and the limiting amount of ammonia adsorbed in the micropores. This behaviour had been reported earlier for the adsorption of short alcohols, but with a single DR plot, due to the fact that specific and non-specific interactions were similar. For carbons with little oxygen on the surface, NH3 adsorption leads to a single DR plot, irrespective of the average pore-size.